The Evaluation System Of Public Education In Minas Gerais: Impacts In Uberlândia's Fundamental School - Maria Juliana de Almeida e Silva (Universidad Autónoma de Madrid, 2018)
The present article is based in a qualitative research that propose to analyze the impacts of the Mineral Evaluation System of Public Education - SIMAVE - in the pedagogical work organization in fundamental education of Uberlândia- MG. Important was the study of the quality and the relationship with evaluation, considered as a way to reach it. The results of the research demonstrated that SIMAVE is as response for urgent evaluation directions, indicated by knew Evaluating State's paradigm, present in many countries as a control instrument of the government for educative institutions. The conclusions demonstrated that democratic, decentralized, participative and equitable principles, in which the SIMAVE is based, aren't materialized get in studied schools. The circumstance in witch institutions get involved with the program and the way it was practice, make the teachers have the feeling of been the object of evaluation. It has been made clear that, after the evaluation results, educators are generally very much concerned with the longing, more incisive and continuos measures expected from the government.